﻿Spatial decoupling of taxon richness, phylogenetic diversity and threat status in the megagenus Erica (Ericaceae) - Pirie, Michael D; Bellstedt, Dirk U; Bouman, Roderick W; Fagúndez, Jaime; Gehrke, Berit; Kandziora, Martha; Le Maitre, Nicholas C; Musker, Seth D; Newman, Ethan; Nürk, Nicolai M; Oliver, E G H; Pipins, Sebastian; et al. (PhytoKeys, 2024)
Estimates of the number of vascular plant species currently under threat of extinction are shockingly high, with the highest extinction rates reported for narrow-range, woody plants, especially in biodiversity hotspots with Mediterranean and tropical climates. The large genus Erica is a prime example, as a large proportion of its 851 species, all shrubs or small trees, are endemic to the Cape Floristic Region (CFR) of South Africa. Almost two hundred are known to be threatened and a further hundred are 'Data Deficient'. We need to target conservation efforts and research to fill the most problematic knowledge gaps. This can be especially challenging in large genera, such as Erica, with numerous threatened species that are closely related. One approach involves combining knowledge of phylogenetic diversity with that of IUCN threat status to identify the most Evolutionarily Distinct and Globally Endangered (EDGE) species. We present an expanded and improved phylogenetic hypothesis for Erica (representing 65% of described species diversity) and combine this with available threat and distribution data to identify species and geographic areas that could be targeted for conservation effort to maximise preservation of phylogenetic diversity (PD). The resulting 39 EDGE taxa include 35 from the CFR. A further 32 high PD, data deficient taxa are mostly from outside the CFR, reflecting the low proportion of assessed taxa outside South Africa. The most taxon-rich areas are found in the south-western CFR. They are not the most phylogenetically diverse, but do include the most threatened PD. These results can be cross-referenced to existing living and seed-banked ex situ collections and used to target new and updated threat assessments and conservation action.
Keywords: heathers; phylogeny; large genera; Conservation prioritisation; threatened species